2010
DOI: 10.1111/j.1749-6632.2009.05085.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell–derived cardiomyocytes can mobilize 1,4,5‐inositol trisphosphate–operated [Ca2+]i stores

Abstract: Because previous findings showed that in human embryonic stem cell-derived cardiomyocytes (hESC-CM) the machinery for Ca2+-induced release of calcium is immature, we tested the hypothesis that hESC-CM contain functional 1,4,5-inositol triphosphate (IP3)-operated intracellular Ca2+ ([Ca2+]i) stores. We investigated the effects of angiotensin II (AT-II) and endothelin 1 (ET-1), which activate the 1,4,5-IP3 pathway, on [Ca2+]i transients and contractions in hESC-CM. Our major findings were that in hESC-CM, both A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…Ca 2+ sparks were also identified by confocal Ca 2+ imaging 45, 46, 47. The involvement of IP 3 -dependent Ca 2+ release in intracellular Ca 2+ transient was demonstrated in human ESC-CMs by using angiotensin II (AT-II) and endothelin 1 (ET-1), which activate the IP 3 R-mediated Ca 2+ release 48 . As Ca 2+ exclusion pathways, SERCA2 and NCX were expressed at levels comparable to those of the adult porcine myocardium.…”
Section: Calcium Handlingmentioning
confidence: 96%
“…Ca 2+ sparks were also identified by confocal Ca 2+ imaging 45, 46, 47. The involvement of IP 3 -dependent Ca 2+ release in intracellular Ca 2+ transient was demonstrated in human ESC-CMs by using angiotensin II (AT-II) and endothelin 1 (ET-1), which activate the IP 3 R-mediated Ca 2+ release 48 . As Ca 2+ exclusion pathways, SERCA2 and NCX were expressed at levels comparable to those of the adult porcine myocardium.…”
Section: Calcium Handlingmentioning
confidence: 96%
“…Many studies of hESC-CMs have demonstrated varying degrees of structural and contractile organization -- in particular the presence of cross-striations, as well as the contractile proteins troponin, myosin heavy chain, tropomyosin, and α-actinin (Binah et al, 2007; Boudou et al, 2011; Caspi et al, 2007a; Dolnikov et al, 2005; Fu et al, 2010; Habeler et al, 2009; Kehat et al, 2001; Kim et al, 2010; Liu et al, 2007; Mummery et al, 2003; Otsuji et al, 2010; Pekkanen-Mattila et al, 2009; Schaaf et al, 2011; Sedan et al, 2010; Sedan et al, 2008). Additionally, mechanical contraction has been measured in both hEBs (Binah et al, 2007; Brito-Martins et al, 2008; Pillekamp et al, 2009; Pillekamp et al, 2007; Schaaf et al, 2011; Sedan et al, 2010; Sedan et al, 2008) and isolated hESC-CMs (Abdul Kadir et al, 2009; Germanguz et al, 2011).…”
Section: Contractilitymentioning
confidence: 99%
“…Additionally, mechanical contraction has been measured in both hEBs (Binah et al, 2007; Brito-Martins et al, 2008; Pillekamp et al, 2009; Pillekamp et al, 2007; Schaaf et al, 2011; Sedan et al, 2010; Sedan et al, 2008) and isolated hESC-CMs (Abdul Kadir et al, 2009; Germanguz et al, 2011). Contraction of hEBs increased with an increase in extracellular calcium concentration (Pillekamp et al, 2009; Schaaf et al, 2011), addition of isoproterenol (Brito-Martins et al, 2008; Schaaf et al, 2011), addition of adrenaline (Apati et al, 2012) and IP3R activation (Sedan et al, 2010; Sedan et al, 2008). Consistent with the findings of immature or absent calcium cycling described in the next section, agents that block RyR release or SERCA uptake had no effect on contraction amplitude in hEBs (Binah et al, 2007; Dolnikov et al, 2005; Dolnikov et al, 2006).…”
Section: Contractilitymentioning
confidence: 99%
“…As observed in foetal cardiomyocytes, hESC-derived cardiomyocytes exhibited the I f channel and showed a low V max . Moreover, immaturity of intracellular Ca 2+ handling of hESC-derived cardiomyocytes was reported, although to a different extent (Dolnikov et al 2006; Liu et al 2007; Satin et al 2008; Zhu et al 2009; Sedan et al 2010). …”
Section: The Potential Of Human Pluripotent Stem Cell-derived Cardiommentioning
confidence: 99%